The Effectiveness of Gadget in Speaking Arabic as a Foreign Language During the Covid 19 - Mokhtar, Mohd Ieruwan Mohamed (American Journal of Social Sciences and Humanities, 2021)
In the 4th Industrial Revolution (IR 4.0) era, learning a foreign language including Arabic has continued to become challenging for non-native speakers besides it has been identified as one of the difficult foreign languages around the world, according to the UNESCO report. To overcome this, the contemporary Arabic language students are practically being engaged with different technological gadgets in mastering the language. Nevertheless, the story is different for students facing connectivity and technological barriers. In general, the advancement of technology in line with IR 4.0 has undoubtedly helped in making the learning process more resourceful than usual. The technology equipment has been helping educators to communicate knowledge effectively. The use of technological tools is essential in facilitating learning processes, especially in languages which is a productive skill. However, many parties have been facing challenges of coping with the frequent changes and advancements in technology as it moves fast. Likewise, ethics in education while using these gadgets during the learning process must be observed. As the objectives of this study is to investigate and identify the effects that contribute to the difficulties in learning Arabic, the implementation of technological gadgets in learning a language is significant. It empowers the learners to practice throughout the learning process while addressing their needs. This helps educators change their negative perceptions of teaching the Arabic language as a foreign language by using any technological gadget. This paper is a theoretical study (conceptual) and not a research paper. The methodology used was the descriptive qualitative method.